Sensitivity analysis of earthquake characteristics in relation to changes in source parameters - Montaño, Byron P. (College of Engineering, University of the Philippines Diliman, 2018)
The imminent occurrence of strong earthquakes in the Philippines, being located in the Pacific Ring of Fire, drives the development of research to further understand this devastating phenomenon. These strong ground motions can be traced from three set of parameters: site, path and source. The latter includes the properties of the fault such as dip angle, plane size and location of the hypocenter as well as the stress drop. These source parameters are studied through simulation of synthetic earthquakes by stochastic finite-fault modeling to predict the resulting strong ground motion. This paper aims to determine the behavior of common earthquake properties as a result of changes in the source parameters from the simulation of the idealized model. The effects of variation and the relationships between parameters are observed and determined through 2D choropleth mapping and exploratory data analysis. It is formulated from the exploratory data analysis that the relationship of earthquake responses and the hypocentral distance has a negative slope. In relation to this formulation, it can be observed that the concentration of strong responses starts propagating from the apparent hypocenter and dissipates farther away. Generally, changes in the source parameters that bring the hypocenter closer to the Earth surface has observed increase in responses. Increase is also observed in strengthening of the stress drop and bringing the hypocenter closer to the midpoint of the length. In terms of changes in fault plane size, compact areas produce responses in more compact areas tend to have stronger but concentrated responses in a smaller area while slender areas tend to have relatively weaker but elongated area of responses. The predominant period, however, displayed no direct correlation to hypocentral distance from the analysis methods performed. The generated choropleth maps provides outright expectations on how an earthquake will behave given its properties while the exploratory data analysis results provides idea of the relationship of the parameters being studied. Both results can be utilized in further understanding the phenomenon in earthquake engineering and disaster risk management